Complicaciones neurológicas en niños con antecedente de Hemorragia Intraventricular atendidos en el Hospital Regional Docente de Trujillo 2015-2019 - Peralta Tingal, Henrry Nilson (2020)
Intraventricular hemorrhage (IVH) is a common complication in premature newborns. This brain injury represents a major problem due to the increasing number of very low birth weight newborns annually and their increased survival. In this sense, the objective of this research project is to describe the neurological complications in premature newborns with a history of intraventricular hemorrhage at two years of age, through the review of medical records of patients who were treated at the Regional Teaching Hospital of Trujillo between 2015 and 2019 through a descriptive, retrospective and cross se